The cyber conceptual framework for developing military doctrine. Issue 3 (2nd July 2016) - Ormrod, David; Turnbull, Benjamin
Abstract: Militaries rely on secure communications. Despite the permeation of cyber-systems throughout the operational environment, there is little readily available doctrine on cyber-warfare. Doctrine that does exist has not been coherently integrated. This paper introduces a Cyber Conceptual Framework, consisting of five questions pertinent to the future use of cyberspace. The authors enunciate a definition of cyberspace, expand on existing military doctrine to reject the conceptualisation of cyberspace as a domain, define cyber-conflict, define cyber-attack and describe the four components and five levels of a cyber-attack. This work develops a common framework from available doctrine and a lexicon for future discussion.